Ovulatory Shifts in Sexual Desire But Not Mate Preferences: An LH-Test-Confirmed, Longitudinal Study. (8th May 2019) - van Stein, K. R.; Strauß, B.; Brenk-Franz, K.
The presented data are part of a longitudinal within-subject study designed to examine ovulatory shifts in human sexuality in a diverse German sample using validated questionnaires. The final sample consists of 78 individuals (76 female, 2 agender) who declared to be mainly or exclusively attracted to males. Questionnaires were completed anonymously online at three cycle phases. Following the gold standard, the fertile window was calculated through the reverse cycle day method and confirmed via urinary tests detecting luteinizing hormone. The questionnaire included the Sexual Desire Inventory, Dresdner Body Image Inventory, the Revised Sociosexual Orientation Inventory, and an adjective list to measure mate preferences. One hundred eighty-four questionnaires were included in the data analysis using linear mixed models. Findings support previous research reporting heightened sexual desire and an improved body image during the fertile window. No shifts were found for mate preference or sociosexual orientation, thus adding to a growing body of literature contesting parts of the ovulatory shift hypothesis.